ABC's of relationship selling / Charles M.Futrell - Charles, M.Futrell
ABC's was conceived as a method of providing ample materials for readers to construct their own sales presentations after studying the text. This gives the instructor the flexibility of the focusing on the "how-to-sell" approach within the classroom. Covering the basic foundations for understanding the concepts and practices of selling in a practical, straightforward, and readable manner, it provides students with a guide to use in preparing sales presentations and role-playing exercises.